TEACHING ENGLISH LANGUAGE AND CULTURE THROUGH ENGLISH LITERATURE - Muth’im, Abdul (Vidya Karya Jurnal Kependidikan, 2015)
It is commonly believed that learning language is also understood as learning culture. This means that when somebody learns a new language, say for example, English, he or she will automatically also learn English culture. In some cases, this belief may be true. In other cases, however, the direction of learning language and culture is not always linear. A sentence produced by a language learner may linguistically and culturally be correct for the other learners of the same language background, but when it is spoken to someone else of different language background it might cause misunderstanding. This misunderstanding occurs not because of the words used in the sentence are weird or the grammar applied is violating the rule of English language system, but it is because of the utterance is not culturally accepted. Â It is this difference of culture that causes such kind ofÂ misunderstanding. To this phenomenon the teaching of literature is assumed to be able to minimize this misunderstanding.Â Â